Fathers' involvement in the healthcare of their children: a descriptive study in southwest Nigeria - Olubunmi Temitope Bodunde; Oluwafolahan Oluwagbemiga Sholeye; Olubukunonla Ayodele Jeminusi; Haroun Adetunji Ajibode; Taibat Olusola Otulana; Emmanuel Olusegun Adebayo (SpringerOpen, 2023)
Abstract Objective This study aims at determining why fathers do not follow their children to the clinic or hospital and exploring the factors that will promote father's participation in healthcare of their children. Design Descriptive cross-sectional study. Setting Community (Sagamu township of Sagamu Local Government Area of Ogun State LGA, Nigeria). Participants All fathers ≥ 18 years that have ever had children, selected from 3 wards in Sagamu township of Sagamu LGA. Results A total of 416 fathers participated in the study. The mean age of participants was 42.0 ± 12.7 years. Forty-four-point five percent (44.5%) had secondary education, while 36.6% were unskilled workers. Forty-two-point three percent (42.3%) said it is a woman's job to take children to the hospital, while about half of the respondents said following a child to the hospital is time-consuming. About 2/3rd of the participants said waiting time in the hospital is too long, while 53.6% will rather go in search of money than go with a child to the hospital. Thirty-nine-point nine percent will need paternity leave to be more involved. Conclusion The major individual factors influencing father's involvement in the healthcare of their children in this study are semi-skilled occupation, marital status, and work schedule. Majority do not think paternity leave is required before fathers can be involved in the healthcare of their children. Intensive health education by healthcare practitioners will improve male participation in children's health.